OAuth 2.0 identity and access management patterns : a practical hands-on guide to implementing secure API authorization flow scenariaos with OAuth 2.0 /: a practical hands-on guide to implementing secure API authorization flow scenariaos with OAuth 2.0. (2013) - Unknown
No abstract available